Exploring experiences of a telephone crisis support workplace training program in Australia. (11th June 2022) - Gilmore, Amanda; Saheb, Rowena; Reis, Arianne
Abstract: Telephone crisis support (TCS) is considered by the World Health Organization to be an integral part of an effective suicide prevention framework. However, as TCS lines worldwide are primarily staffed by volunteers, they frequently experience high staff turnover impacting on their ability to provide crucial crisis counselling to the population. One group that has been identified as potentially lessening staff shortages is university students, who may be attracted to TCS as a way to gain professional experience and qualifications. However, challenges are associated with the recruitment of this cohort, due to the potential impacts working in crisis support may have on the well‐being of a group that is identified as being at higher risk of poor mental health. This study used semi‐structured interviews, conducted between March and May 2020, to explore university students' experiences of a Crisis Support Workplace Training Program. It included 16 university students who completed (fully or partially) the training programme. Thematic analysis was used to identify patterns across the dataset. NVivo 12© was used throughout the analysis to assist with organisation and coding of data. Two overarching themes were identified: 1) Becoming and being the role, and 2) Experiencing and managing barriers to helping. Results illustrate how students experienced varying levels of distress due to empathetic engagement with callers, while also highlight the impact of students' experiences on the development of their professional identities. This study is amongst the first to examine the perceptions and experiences of training for and delivering TCS, and the first to focus specifically on university students as volunteer workers. The study's findings highlight the challenges participants face in undertaking crisis support training and our discussions provide a range of recommendations for future practice and research.